Potential of Topical Curcumin in Reduction of TNF-α expression and Synovium Hyperplasia on Wistar Rats of Rheumatoid Arthritis Model - Ferri Widodo; Diana Lyrawati; Bagus Putu Putra Suryana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2016)
Rheumatoid arthritis is a chronic inflammatory autoimmune disease associated with articular and systemic effects. This disease affects synovial joints covered by a special tissue called synovium. Curcumin has a potent antioxidant, antiinflammatory agent, antiangiogenic and anticarcinogenic. Curcumin can downregulate the expression of various proinflammatory cytokines and is reported beneficial effects in arthritis, but has a poor solubility dan bioavailability as well. The purpose of this research was to study the potential of liposomes topikal curcumin in reducing athritis score, reducing the expression of TNF-α and histopathological synovium hyperplasia of hind paw on Wistar rats with CFA that had been treated with topical curcumin. In this study, rats were divided into 7 groups: positive control, negative control, rheumatoid arthritis with topical curcumin therapy of 90 mg/kg BW, rheumatoid arthritis with topical curcumin therapy of 110 mg/kg BW, rheumatoid arthritis with topical curcumin therapy of 200 mg/kg BW, rheumatoid arthritis with methotrexate therapy, rheumatoid arthritis with placebo therapy. Results from this experiment indicated that topical curcumin has no significant to the arthritis score, significantly effect to percentase expression of TNF-α (p<0.05) and could decrease synovium hyperplasia based on histophatology examination. It could be concluded that therapy of topical curcumin could decrease the expression of TNF- α and synovium hyperplasia in rheumatoid arthritis rat.